STRATEGI KOMUNIKASI PEMASARAN PARIWISATA BANYU MILI DALAM PENINGKATAN JUMLAH PENGUNJUNG - Rohimah, Afifatur (Universitas 17 Agustus 1945 Surabaya, 2017)
Tourism becomes the main source of income that shifts the existence of mining business. Tourism objects in the district wonosalam jombang district is very diverse but dominated by the potential of nature tourism. One of the popular natural attractions in the district wonosalam is djawi village, banyu mili and pine forests are all located in the village carang wulung. But the fact that the number of visitors increase the number of crucial problems experienced by the manager. One effort to be able to increase the number of tourist visits is a marketing communication marketing strategy. This study focuses on descriptive qualitative research. The result of the research shows that the important elements in marketing mix are personla selling, advertising, publication, promotoin sales, and sponsorship. Kampung djawi shows that the five mixes have been applied and are continuously improved from various aspects, in contrast to banyu mili and pine forests whose marketing capabilities have been applied to only publications and personal selling. While the limitations of human and financial resources to be a barrier in the application of sponsorship, advertising, and sales promotion. Based on these data, it is obvious that the number of tourist visits of djawi kampung tend to increase gradually, while banyu mili and pine forests tend to be stable and stagnant. Keywords: Tourism, Marketing Strategy, Communication